Power, recovery and doing something worthwhile: A thematic analysis of expert patient perspectives in psychiatry education - Katie Ward; Miriam Stanyon; Karl Ryan; Professor Subodh Dave (Wiley, 2022)
Abstract Background Patient involvement in psychiatry education is required by policy and has many benefits for students. Little research has focused on the impact on expert patients (EPs). Objective This study aimed to explore the impact of involvement in psychiatry education on mental health patients. Design A qualitative descriptive study using semistructured interviews was conducted in a psychiatry teaching unit in the East Midlands, UK. A purposive sample of 20 EPs involved in teaching was interviewed about the social and psychological impacts of involvement. Transcripts were analysed thematically and a coding scheme was developed. Results Five themes were identified: shaping the doctors of the future-something worthwhile, challenging assumptions about mental health, recovery and transformation, vulnerability and support and expertise and power. Conclusion These EPs benefitted from their experience of teaching. Involvement in psychiatry teaching may require putting oneself in a vulnerable position, but a supportive and open faculty team may mitigate this challenge. The Expert Patient Programme was seen as a way of helping to reduce the power difference between patients and doctors in the future. There is a need to examine the language that we use to talk about patient involvement as this may have implications for this power dynamic. The context and mechanisms that lead to the benefits described by participants should be studied so that these benefits may be generalized to other contexts. Patient Contribution An EP was involved in the planning and ethical approval application process of the project and the drafting and approval of this manuscript.